Strategic HR practices and sustainable competitive advantage in Bahrain - Almuslamani H.A.I.; Daud S. (American Scientific Publishers, 2023)
The strategic literature has presented a steady progress in better understanding the resources of sustainable competitive advantage. Simultaneously, the resource-based view (RBV) was developed over last years to determine which resources, capabilities, and organizational components lead to the sustainable competitive advantage. Recently, strategic human resources practices have received much attention as key elements to achieve successful competitiveness and gain above-average returns. Drawing on the theoretical perception of the resource-based view, this article articulates the relationship between strategic human resource practices and sustainable competitive advantage. After debating this mutual relationship, this article concludes a conceptual framework. This framework is recommended to be exploited in Bahrain where the Economic Vision 2030 of Bahrain has been implemented since 2008 mainly to reduce the high dependence of the national economy on oil and gas. In particular, the industrial sector (manufacturing sector) gained the governmental support based on sustainability, diversity, and innovation. However, the industrial sector remained without any remarkable advancement and it showed its weakness in resisting to the oil and gas declination. Moreover, industrial sectors still face a shortage of both quality employment and appropriate national skills. Hence, the recommended conceptual framework is expected to support the national efforts in aligning the strategic HR practices to sustain the competitive advantage where these mutual relationships have not empirically received enough attention in the existent literature. 2017 American Scientific Publishers. All rights reserved.